Perbedaan Pola Sidik Jari Manusia Menurut Sains dan Tafsir Qur’an Surat Al-Qiyamah Ayat 3-4 - Moch Naufal Ramdhani; Deden Suparman (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Knowledge in the field of science is increasingly developing day by day following environmental conditions and human thinking. So science, especially in the field of science, should not be separated from religion. In the Al-Qur'an there are many verses that explain the process of human creation, such as in Surah Al-Hajj verse 5, Surah Al-Mukmin verse 67, Surah Az-Zumar verse 7, Surah Fathir verse 11, and many more. . someone can observe humans through biological observations. In the Qur'an, humans are often called